Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1371/journal.pone.0055898
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of New Zealand Kanuka, Manuka and Clover Honeys on Bacterial Growth Dynamics and Cellular Morphology Varies According to the Species

Abstract: Treatment of chronic wounds is becoming increasingly difficult due to antibiotic resistance. Complex natural products with antimicrobial activity, such as honey, are now under the spotlight as alternative treatments to antibiotics. Several studies have shown honey to have broad-spectrum antibacterial activity at concentrations present in honey dressings, and resistance to honey has not been attainable in the laboratory. However not all honeys are the same and few studies have used honey that is well defined bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
101
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(110 citation statements)
references
References 46 publications
8
101
0
1
Order By: Relevance
“…In the present study, honey E had the second best activity after honey F. In honey E, the major nectar source was clover. Clover honey has been reported to possess antimicrobial activity against Pseudomonas aeruginosa (Lu et al 2013). In honeys B and C, the antimicrobial activity was quite equal.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, honey E had the second best activity after honey F. In honey E, the major nectar source was clover. Clover honey has been reported to possess antimicrobial activity against Pseudomonas aeruginosa (Lu et al 2013). In honeys B and C, the antimicrobial activity was quite equal.…”
Section: Resultsmentioning
confidence: 99%
“…Though not the sole active component, hydrogen peroxide was credited with a partial antibacterial activity. 36,37 For effective wound management, the anti-biofilm effect of manuka honey was investigated against Proteus mirabilis and Enterobacter cloacae wound isolates. The micro-titer plate assay revealed that the honey at a sub-inhibitory concentration of 10% (w/v) significantly reduced the biofilm development of both isolates.…”
Section: Anti-bacterial Anti-biotic and Anti-viral Effectsmentioning
confidence: 99%
“…honey is renowned for its antimicrobial activity, primarily attributed to methylglyoxal (MGO) (Kwakman et al, 2010). MGO alone or in manuka honey is a potent antimicrobial compound in vitro (Ferguson et al, 1998; Kwakman et al, 2010; Lu et al, 2013). Consumption of manuka honey may deliver antimicrobial MGO, prebiotic honey oligosaccharides or bioactive phytochemicals to the gut.…”
Section: Introductionmentioning
confidence: 99%